Numerical study of flow past a circular cylinder using SSTκ-ω, LES and ELES formulations. (2015) - Hu, H.Z.; Hu, H.X.; Jiang, S.L.; Zheng, Y.G.
A comparison study of the flow past a circular cylinder is carried out using SSTκ-ω, LES and ELES models according to the practical conditions in a steam generator of a nuclear power plant. The behaviour of different models in predicting the flow field, velocity distributions, hydrodynamic forces and their computational costs is evaluated by the published data. The results show that the three models can predict the gradual and symmetrical distributions of three pairs of the recirculation regions behind the cylinder. However, they behave differently in predicting the separation angles, hydrodynamic forces and CPU time. The present work has benefits for better understanding the flow past obstacles and the associated flow-induced vibration.